New perspectives in the management of acute pancreatitis – focus on antibiotic prophylaxis, management of necrosis and COVID-19 implications - Woźniak, Aleksandra; Cioch, Michał Jakub; Nowak, Julia; Hermanowicz, Kamil; Kaczmarska, Urszula; Doman, Katarzyna; Najdek, Agnieszka; Oleksy, Daria; Komada, Dawid; Mycyk, Marcin (Journal of Education, Health and Sport, 2025)
This review highlights the recent development in the management of acute pancreatitis in the area of antibiotic prophylaxis, management of necrosis and correlation with SARS-CoV-2 infection. The evidence from recent studies has not shown a significant benefit of administration of antibiotic prophylaxis in acute pancreatitis. Additionally, a few trials draw attention to the disadvantages of prophylactic use of antibiotics. However, in this area more trials have to be conducted. When it comes to management of necrosis, the recent data recommends a postponed drainage. Delayed procedure is considered now as preferential treatment. Furthermore, delayed drainage is associated with fewer interventions and necrosectomies compared to immediate drainage. There is still insufficient data to confirm the influence of SARS-CoV-2 infection on the development and course of pancreatitis. Special attention should be brought to all COVID-19 patients presenting with gastrointestinal symptoms. Measurement of amylase and/or lipase levels in the serum is recommended for preliminary diagnosis. If suspicion arises, full diagnosis of acute pancreatitis should be conducted for early implementation of supportive treatment.